1 Peter: a critical and exegetical commentary : volume 2: chapters 3-5 - Horrell, David G. (International Critical Commentary, 2023)
The second volume in Travis B. Williams' and David G. Horrell's magisterial ICC commentary on first Peter. Williams and Horrell bring together all the relevant aids to exegesis - linguistic, textual, archaeological, historical, literary, and theological - to help the reader understand the letter. This second covers the major part of the letter, providing commentary on 2.11 to the end of the letter. The exegesis provides for each passage sections on bibliography, text-criticism, literary introduction, detailed exegesis, and overall summary. The volume concludes with a comprehensive bibliography, which covers the whole epistle